Sedimentology and geochemistry of the contact between the Napo and Tena formations at the Puerto Napo outcrop, Tena: deciphering changes in depositional conditions in the Oriente Basin, Ecuador (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
This study characterizes the contact between the Napo and Tena formations at the Puerto Napo outcrop in the Oriente Basin of Ecuador through sedimentological, petrographic, and geochemical analyses. The results indicate that the boundary between both units corresponds to a gradual transition, without evidence of erosive surfaces or unconformities. The Napo Formation is composed of carbonate lithologies with abundant planktonic microfauna, whereas the Tena Formation is dominated by siliciclastic sandstones and siltstones with Andean terrigenous input and volcanic fragments. Geochemical profiles (Ca/Fe, Ca/Si, Ca/Ti, Ca/Al, Ca/Sr) display a gradual trend from the Napo to the Tena formations, reflecting the progressive decrease in marine influence and the increase in continental input. Total organic carbon (TOC) showed variability within the Napo Formation, with values reaching up to 0.8%, whereas the Tena Formation exhibited low and stable values (0.1–0.3%). Magnetic susceptibility presented low values in the Napo Formation, associated with a marine carbonate-dominated environment, and higher values in the Tena Formation, linked to a greater content of ferromagnesian minerals. These results support the interpretation of a transitional contact related to a transgressive–regressive event during the Maastrichtian, controlled by eustatic and tectonic processes.